Performance of castor (Ricinus communis L) hybrids and varieties under rainfed conditions in Alfisols: Performance of castor (Ricinus communis L) hybrids and varieties under rainfed conditions in Alfisols - R MOHAN KUMAR; YAMANURA (Journal of Oilseeds Research, 2020)
An experiment was conducted to study the performance of seven hybrids/varieties of castor for their adaptability and yield potentiality. GCH-8 recorded significantly higher seed yield of castor (2369 kg/ha) and was statistically superior over rest of the cultivars. Seed yield of GCH-8 in each harvest was 961, 698 and 710 kg/ha at primary, secondary and tertiary spikes respectively.